The Ukraine war and its food security implications in Nepal - Bhatta, Astha (International Food Policy Research Institute, 2022)
Though declining in importance as Nepal undergoes structural transformation, agriculture still accounts for 23.9% of GDP and one in five people was employed in the sector with a larger share of women (33 percent) employed in agriculture than men (14.7 percent) (Labor survey of 2017-18). While not directly employed in agriculture, approximately 60 percent of the population has some engagement with the sector.